Respuesta :

Answer:

x = 2

Explanation:

[tex]\sf \rightarrow (x+1)(x + 2) = x(x+7)-6[/tex]

distribute

[tex]\sf \rightarrow x^2 + 2x + x + 2 = x^2 + 7x - 6[/tex]

simplify

[tex]\sf \rightarrow x^2 + 3x + 2 = x^2 + 7x - 6[/tex]

isolate x coefficient's to the left side and integers to the right side

[tex]\sf \rightarrow x^2 + 3x -x^2-7x = - 6-2[/tex]

collect similar terms

[tex]\sf \rightarrow x^2 -x^2+ 3x-7x = - 6-2[/tex]

simplify

[tex]\sf \rightarrow -4x = - 8[/tex]

divide both sides by -4

[tex]\sf \rightarrow \dfrac{-4x}{-4} = \dfrac{- 8}{-4}[/tex]

simplify

[tex]\sf \rightarrow x = 2[/tex]

Answer:

x = 2

Step-by-step explanation:

(x + 1)(x + 2) = x(x + 7) - 6 ← expand left side using FOIL and distribute right side

x² + 3x + 2 = x² + 7x - 6 ( subtract x² from both sides )

3x + 2 = 7x - 6 ( subtract 7x from both sides )

- 4x + 2 = - 6 ( subtract 2 from both sides )

- 4x = - 8 ( divide both sides by - 4 )

x = 2